2022
DOI: 10.1021/acsaem.2c01709
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Acid-Functionalized Metal–Organic Frameworks as Excellent Precursors toward Bifunctional Metal-Free Electrocatalysts

Abstract: Metal–organic frameworks (MOFs) are promising precursors for synthesizing functional carbon materials, and their atomic-scale designs have recently been studied for improving their performance. Herein, we synthesized an alanine-decorated MOF-5 via a solvothermal method using a mixture of dimethylformamide and water as the solvent. Experimental and computational investigations revealed that alanine residues were located in the micropores of MOF-5 due to interactions between the MOF Zn clusters and the carboxyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…used alanine modified MOF‐5 carbonized at 1100 °C as an electrocatalyst for ORR and HER, showing good activity using a single nitrogen configuration in the lamellar pores. [ 81 ] In this work, the authors found by grand‐canonical Monte Carlo simulations that the uniform micropores of pristine MOF‐5 disappeared the sharp peak at 0.78 nm compared to the precursor, and that A/MOF/x (alanine‐treated MOF‐5) exhibited a wider peak than that of pristine MOF‐5. It reveals that the chemical interaction between alanine and the structural units of MOF‐5 affects the ordered pore structure.…”
Section: Computational Methods and Advanced Characterization/monitori...mentioning
confidence: 88%
See 1 more Smart Citation
“…used alanine modified MOF‐5 carbonized at 1100 °C as an electrocatalyst for ORR and HER, showing good activity using a single nitrogen configuration in the lamellar pores. [ 81 ] In this work, the authors found by grand‐canonical Monte Carlo simulations that the uniform micropores of pristine MOF‐5 disappeared the sharp peak at 0.78 nm compared to the precursor, and that A/MOF/x (alanine‐treated MOF‐5) exhibited a wider peak than that of pristine MOF‐5. It reveals that the chemical interaction between alanine and the structural units of MOF‐5 affects the ordered pore structure.…”
Section: Computational Methods and Advanced Characterization/monitori...mentioning
confidence: 88%
“…The application of Monte Carlo molecular simulation methods to simulate chemical reactions, especially in pores, is one of the more cutting-edge and emerging research directions in the field of molecular simulation. [80][81][82] This method is able to observe the pore size, shape, surface non-uniformity and other properties of catalytic materials, as well as the effects of temperature, pressure and other variables on the equilibrium and kinetics of chemical reactions from the molecular microscopic level, so as to better grasp the essential characteristics of chemical reactions. For instance, Shu et al used alanine modified MOF-5 carbonized at 1100 °C as an electrocatalyst for ORR and HER, showing good activity using a single nitrogen configuration in the lamellar pores.…”
Section: Density Functional Theory Calculations Machine Learning and ...mentioning
confidence: 99%
“…Additionally, a N peak was not observed on the as-synthesized Nb 2 CT x MXene. Figure e shows the HR scan of N1 s, which consists of a peak at 399.5 eV that could be attributed to amine groups, while the other peak at 401.5 eV can be assigned to protonated amines …”
Section: Resultsmentioning
confidence: 99%
“…Figure 2e shows the HR scan of N1 s, which consists of a peak at 399.5 eV that could be attributed to amine groups, while the other peak at 401.5 eV can be assigned to protonated amines. 56 Electrochemical Analysis. The electrochemical performance of the CY electrode modified with Zn-MOF, Nb Ultimately, the optimal pH for the electrocatalytic oxidation of MEL was determined to be 7.2.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the nitrogen-heteroatoms need to be incorporated exteriorly in a controllable manner. 16,17 To this end, we envision that Zn-MOFs with mixed azolate and terephthalate ligands (herein denoted as Zn-MOF-mix) might be a better option since they perfectly merge the merits of the abovementioned two types of Zn-MOFs. Nonetheless, it remains scarce to apply Zn-MOF-mix to prepare metal-free carbon materials.…”
mentioning
confidence: 99%